2020
DOI: 10.1038/s41467-020-18289-9
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational inheritance of impaired larval T cell development in zebrafish

Abstract: Evidence for transgenerational inheritance of epigenetic information in vertebrates is scarce. Aberrant patterns of DNA methylation in gametes may set the stage for transmission into future generations. Here, we describe a viable hypomorphic allele of dnmt1 in zebrafish that causes widespread demethylation of CpG dinucleotides in sperm and somatic tissues. We find that homozygous mutants are essentially normal, with the exception of drastically impaired lymphopoiesis, affecting both larval and adult phases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…We additionally annotated cluster 35 as immune cell progenitors as it showed an enrichment of several genes involved in larval hematopoietic development including ikzf1 and genes involved in cell cycle regulation and proliferation, such as the proliferation marker pcna . Cluster 35 also contains markers of lymphocytes, which start to develop during larval life, including rag1 and zap70 (Iwanami et al ., 2020). In the neutrophil cluster 72, genes enriched in the presence of microbiota encoded characteristic immune cell functions including threat sensing, chemotaxis and cell shape changes, and cellular processing (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We additionally annotated cluster 35 as immune cell progenitors as it showed an enrichment of several genes involved in larval hematopoietic development including ikzf1 and genes involved in cell cycle regulation and proliferation, such as the proliferation marker pcna . Cluster 35 also contains markers of lymphocytes, which start to develop during larval life, including rag1 and zap70 (Iwanami et al ., 2020). In the neutrophil cluster 72, genes enriched in the presence of microbiota encoded characteristic immune cell functions including threat sensing, chemotaxis and cell shape changes, and cellular processing (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, zebrafish inherit the paternal DNA methylome configuration ( Jiang et al., 2013 ; Potok et al., 2013 ) ( Table 1 ). Recent studies demonstrated the absence of global DNA methylation erasure in the zebrafish germline and extensive amplification and demethylation of the oocyte-specific fem-rDNA cluster during gonad transformation, which suggested the retention of paternal epigenetic memory in the developing zebrafish germline ( Iwanami et al., 2020 ; Skvortsova et al., 2019 ). These studies have proved the existence of paternal transgenerational epigenetics in non-mammalian (anamniote) vertebrates.…”
Section: Paternal Imprinted Genes and Mechanism Of Paternal Trans-epi...mentioning
confidence: 99%
“…True TEI has been clearly demonstrated in numerous animal models, from C. elegans to fish to mice [3,9,90,98,99], but most of this evidence is from artificial, laboratory-based conditions. How does this translate into the natural environmental context?…”
Section: Environmental Triggers Of Transgenerational Epigenetic Inheritancementioning
confidence: 99%